PERAN KIAI ISKANDAR UMAR ABDULLATIF di KRIAN SIDOARJO - Muhammad Akbar Firdaus (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2021)
Abstract: This study seeks to explore the autobiography of a character, namely Kiai Iskandar Umar Abdullatif in shaping the morals of the Krian community, Sidoarjo, the period 1985-2010. Society has a collective character that can be formed or changed to become more mature—in the assumption that some people are